The Effect of the hot chair strategy on acquiring and maintaining grammatical concepts among middle school students in the grammar subject. - Dhiyab Abdul Ali Al-Rafaei., Qais (Journal of College of Education, 2020)
The current research aims to find out (the effect of the hot chair’s strategy on acquiring and maintaining grammatical concepts among middle school students in the grammar course) To achieve the research goal, the researcher formulated zero hypotheses: There is a statistically significant difference between the experimental group students that were studied according to the hot-seat strategy over the control group students who studied according to the usual method of testing the acquisition of concepts. There is no statistically significant difference at the level of significance (0,05) between the average acquisition of experimental group students who are studying grammar in accordance with the (hot chair) strategy and the average concepts and development of control group students who study grammar in accordance with the traditional method. In light of the findings of the current research, it can be concluded that: The use of the "hot chair" strategy may contribute to increasing the effectiveness of student excellence and their activities, making them the focus of the educational process. To complement the results of the current research, the researcher suggests conducting the following studies: Carry out similar studies to the current study on universities and middle schools.